A Human Resource Management Model Based on Collective Values in Strengthening the Performance of Modern Cooperatives in Indonesia - Jeremiah, Maudi (Universitas Sains dan Teknologi Komputer, 2025)
This research is motivated by the challenges modern cooperatives in Indonesia face in managing human resources (HR) that are not only oriented toward economic efficiency but also maintain collective values such as togetherness, participation, and social responsibility. This research aims to develop a human resource management model grounded in collective values within modern cooperatives. The research method uses a mixed-methods approach with a sequential exploratory design, in which multiple case studies serve as the primary qualitative method, and quantitative data are used only to support. The study was conducted at three cooperatives: Kospin Jasa, Kopkun Cooperative, and Koperasi Setia Kawan. Qualitative data were collected through in-depth interviews, participant observation, and document analysis, and then analyzed using thematic analysis techniques with NVivo 14. The research findings indicate that collective values are concretely operationalized in human resource recruitment, training, and performance evaluation systems, supported by numerical indicators such as the Collectivity Index, and are associated with an average 22% increase in internal productivity. These findings suggest that collective values can be formulated as a structural component in the modern cooperative human resource management model, contributing to organizational performance and sustainability